Mrs. lincoln's sisters ebook A novel. - Chiaverini, Jennifer (2020)
"A fascinating glimpse into the women of an influential family on the front lines of some of the most important moments of that indelible time."—Booklist The New York Times bestselling author of Mrs. Lincoln's Dressmaker returns to her most famous heroine, Mary Todd Lincoln, in this compelling story of love, loss, and sisterhood rich with history and suspense. In May 1875, Elizabeth Todd Edwards reels from news that her younger sister Mary, former First Lady and widow of President Abraham Lincoln, has attempted suicide. Mary's shocking act followed legal proceedings arranged by her eldest and only surviving son that declared her legally insane. Although they have long been estranged, Elizabeth knows Mary's tenuous mental health has deteriorated through decades of trauma and loss. Yet is her suicide attempt truly the impulse of a deranged mind, or the desperate act of a sane woman terrified to be committed to an asylum? And—if her sisters can put past grievances aside—is their love powerful enough to save her? Maternal Elizabeth, peacemaker Frances, envious Ann, and much adored Emilie had always turned to one another in times of joy and heartache, first as children, and later as young wives and mothers. But when Civil War erupted, the conflict that divided a nation shattered their family. The Todd sisters's fates were bound to their husbands' choices as some joined the Lincoln administration, others the Confederate Army. Now, though discord and tragedy have strained their bonds, Elizabeth knows they must come together as sisters to help Mary in her most desperate hour.